Multimodal composing: strategies for twenty-first century writing consultations - Sabatino, Lindsay A., editor; Fallon, Brian, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
Strategies for writing center directors and tutors working with writers whose texts are visual, technological, creative, and performative--strategies most useful for writers and how tutors can develop a better sense of multimodal composing and practices and the relationship between rhetorical choices, design thinking, and technological awareness.--Provided by publisher.
Preface / Brian Fallon and Lindsay A. Sabatino -- 1. Introduction: Design Theory and Multimodal Consulting / Lindsay A. Sabatino -- 2. Storyboard/ing: Multimodal Tool and Artifact / Brandy Ball Blake and Karen J. Head -- 3. Artist and Design Statements: When Text and Image Make Meaning Together / Brian Fallon -- 4. Brochures: Helping Students Make Good Design Decisions / Sohui Lee and Jarret Krone -- 5. Academic Research Posters: Thinking Like a Designer / Russell Carpenter and Courtnie Morin -- 6. Prezi and PowerPoints Designed to Engage: Getting the Most Out of Quick-and-Dirty Pathos / Shawn Apostel -- 7. Infographics: A Powerful Combination of Word, Image, and Data / Alyse Knorr -- 8. ePortfolios: Collect, Select, Reflect / Lauri Dietz and Kate Flom Derrick -- 9. Web-Design Tutoring: Responding as a User / Clint Gardner, Joe McCormick, and Jarrod Barben -- 10. Podcasts: Sound Strategies for Sonic Literacy / Brenta Blevins -- 11. Multimodal Video Projects: Video-Doing by Example / Patrick Anderson and Florence Davies -- 12. Public Service Announcements / PSAs: Focused Messages for Specific Audiences / Alice Johnston Myatt -- 13. Professional Identity and Social Media: Consulting Personal Branding Projects / James C. W. Truman -- 14. Copyright and Citations for Multimedia Sources / Molly Schoen and Sarah Blazer.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Mass media -- Authorship -- Study and teaching (Higher); Visual communication; Oral communication